Positioning Control of Satellite Antenna for High Speed Response Performance - Paulinus Chinaenye Eze; Jude Kennedy Obichere; Ekene Samuel Mbonu; Ondoma James Onojo (Institut Teknologi Sepuluh Nopember, 2024)
Dish antennas are essential elements in establishing communication between satellite and earth station. The response speed of the position control process of a dish antenna mounted on a moving vehicle that communicates via NigComSat-1R with a central control office is affected by round trip or time delay. Therefore, there is need to design a control system that will address this problem in order to achieve high speed positioning response. The mathematical models representing the dynamics of the antenna positioning system were obtained. A back propagation neural network (BPNN) based proportional integral and derivative (PID) controller was designed and added to the antenna position control loop. The resulting system was modelled in MATLAB. Simulation results indicated that it provided a rise time of 0.027 s, settling time of 1.06 s and overshoot of 0% at peak time of 0.06 s. This shows that the response speed of the control process using the designed BPNN-PID is 37 degree per second. Comparison with previous controllers applied to the same system indicated that BPNN-PID controller outperformed all of them. Generally, the BPNN-PID controller is suitable for high speed position control of the antenna and improves overall performance.